Causes of stress on children with ADHD and the role of ICTs - Tsakiridou , Maria; Drigas, Athanasios (Technium BioChemMed, 2022)
The Attention Deficit Hyperactivity Disorder (AD/HD) is the most common neurodevelopmental disorder of childhood and one of the more widespread chronic diseases that affect children school age, based on the DSM-IV. This study focuses on the influence of stress to the kids suffering from ADHD and the importance of other elements on it. This particular study was based on articles in scientific journals, with the purpose to investigate some of the factors that affect positively or negatively in the exacerbation of anxiety on children suffering from ADHD and how the prenatal and parental stress affects this condition. The results have shown that the environmental factors, nutrition, hormones, neurotransmitters and alternative techniques are directly related with the characteristics of the disorder and the ways of how to improve it. In the light of these findings, we came to the conclusion that we can intervene to the deficits of mainly socio-emotional functions through the above factors.